Consumer Attitudes Towards Foreign Branded Apparel in Malaysia - Bhat, Sana Altaf (2016)
This study was carried out to study Generation Y consumer attitudes and the effect of key factors on their intent to purchase foreign branded apparel in Malaysia. The conceptual framework was developed using the theory of reasoned action (TRA). Quantitative research using 320 internet surveys was employed involving local and international university students, mostly aged between 18-35 years. From the results it was found that out of the four variables - brand recall, price discounts, past behavior and attitude towards purchase behavior, only the last two significantly influenced purchase intentions. Past behavior was found to have the strongest impact, followed by attitude. The theory of reasoned action is supported by the findings of this study as a prediction tool to assess consumer purchase intentions. However since the study is only based on one product category and one respondent group, this has limited its generalisability. Further snowball and convenience sampling methods were chosen which may not truly represent the selected audience. Future research may focus on a random and a larger sample, multiple product categories and additional variables added to the model to expand its usefulness. The findings suggest that firms should try to focus more on the Generation Y consumer, enhance the customer shopping experience by maintaining their reliability and credibility, reduce the amount and frequency of discounts and minimize ads to the basics. Both the review of existing papers and the findings will help academics gain useful insights on consumer purchase intentions, while marketers will gain a clear understanding of Generation Y consumer attitudes and purchase intentions and their significance in Malaysia.